The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1051/matecconf/201713803005
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Manufacturing Properties of Solid Capsules for Mixing Cementitous Composite Materials for Self-Healing of Crack

Abstract: Abstract. In this study, we fabricated self-healing solid capsules using cement powder, an inorganic-based material that is the same as that of cement composites. Self-healing solid capsules can be divided into two stages(capsule core preparation and capsule wall coating). First, the capsule core mixes the core material and the coagulant to form a core material dough having a proper quality, and then puts into a capsule core manufacturing machine. the next, it was produced through the pore chamber under the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Spherical (Giannaros et al 2016a(Giannaros et al , 2016bKanellopoulos et al 2016Kanellopoulos et al , 2017Al-Tabbaa et al 2019;Al-Tabbaa 2019, 2020) Cementitious 8 Spherical or tubular (Sisomphon et al 2011;Formia and Irico 2015;Formia et al 2015aFormia et al , 2016Anglani et al 2020aAnglani et al , 2020bRen et al 2020b;Lv et al 2020a) PMMA, PLA, PS 8 Tubular (Hilloulin et al 2015;Araújo et al 2017Araújo et al , 2018Choi et al 2017aChoi et al , 2017bAnglani et al 2019;Rodríguez et al 2020;Wu et al 2020 (Gruyaert et al 2016;Wang et al 2016;Dong et al 2018aDong et al , 2018b Other 11 Spherical or tubular (Ge et al 2011;Van Tittelboom et al 2012;Li et al 2013Li et al , 2016aDong et al 2015;Xiong et al 2015;De Nardi et al 2017;Fang et al 2018;Souza and Al-Tabbaa 2018;Wang et al 2019a;Lv et al 2020b) sules (29 μm average diameter) under SEM (Beglarigale et al 2018), showed that the encapsulated sodium silicate was in the form of spherical solid particles inside the capsules. It was concluded that sodium silicate was consumed due to cracks on the surface of the capsules that allowed an air-drying process to take place.…”
Section: Shell Materials Number Of Papers Geometry Referencesmentioning
confidence: 99%
“…Spherical (Giannaros et al 2016a(Giannaros et al , 2016bKanellopoulos et al 2016Kanellopoulos et al , 2017Al-Tabbaa et al 2019;Al-Tabbaa 2019, 2020) Cementitious 8 Spherical or tubular (Sisomphon et al 2011;Formia and Irico 2015;Formia et al 2015aFormia et al , 2016Anglani et al 2020aAnglani et al , 2020bRen et al 2020b;Lv et al 2020a) PMMA, PLA, PS 8 Tubular (Hilloulin et al 2015;Araújo et al 2017Araújo et al , 2018Choi et al 2017aChoi et al , 2017bAnglani et al 2019;Rodríguez et al 2020;Wu et al 2020 (Gruyaert et al 2016;Wang et al 2016;Dong et al 2018aDong et al , 2018b Other 11 Spherical or tubular (Ge et al 2011;Van Tittelboom et al 2012;Li et al 2013Li et al , 2016aDong et al 2015;Xiong et al 2015;De Nardi et al 2017;Fang et al 2018;Souza and Al-Tabbaa 2018;Wang et al 2019a;Lv et al 2020b) sules (29 μm average diameter) under SEM (Beglarigale et al 2018), showed that the encapsulated sodium silicate was in the form of spherical solid particles inside the capsules. It was concluded that sodium silicate was consumed due to cracks on the surface of the capsules that allowed an air-drying process to take place.…”
Section: Shell Materials Number Of Papers Geometry Referencesmentioning
confidence: 99%
“…Table 3 shows the physical properties of chemical admixtures. The self-healing solid capsule (SHC) used in the experiments was prepared at seven different sizes (2400, 1200, 850, 600, 300, 150, and 75 µm) [31]. Figure 1 shows the SHC used in the experiment and Figure 2 shows the size and extent of SHC.…”
Section: Introductionmentioning
confidence: 99%
“…After that, in order to mix directly with the mortar formulation, it is essential to coat the core material in order to prevent a prior reaction with the mixing water during the mixing process. In this study, mixing water was blocked by applying liquid rubber on the surface of the core material [31]. Figure 3 shows the state before and after surface coating of the core material.…”
Section: Introductionmentioning
confidence: 99%